COMPARATIVE STUDY OF THE EFFECTS OF PROBIOTIC FEED IN CONVENTIONAL AND BIOFLOC CULTURE SYSTEMS ON THE GROWTH OF CATFISH (Clarias sp.) - Syaifullah, Mohammad Mimbri; Martini, Ni Nyoman Dian; Yudasmara, Gede Ari (Jurusan Perikanan dan Kelautan, 2025)
This research was carried out to determine the effect of probiotic feed on the growth of catfish (Clarias sp.) in two different culture systems. This research was carried out for 30 days using a randomized block design method, namely K (conventional group) and B (biofloc group), each with 3 replications. The data studied were catfish growth, survival, feed conver-sion and feed efficiency. Data collection was carried out 3 times, namely at the beginning, middle and end of the research. Growth and survival data were tested using the non-parametric Mann-Whitney U-test. The results showed that there were differences in catfish growth (P<0.05) in conventional and biofloc culture systems. The con-ventional group produced an average absolute weight of 5.9 grams and the biofloc group produced 6.3 grams. The absolute length of catfish in the conventional group averaged 10.1 cm and in the biofloc group it was 11.1 cm. Catfish survival data showed there was a significant difference (P<0.05). The survival value in the conventional group was 83%, while in the biofloc group it was 93.3%. The FCR value in the conventional group was 1.4 and in the biofloc group was 1.3. Catfish in the conventional group got a feed efficiency of 49% and in the biofloc group it was 51%.Keywords: Biofloc, Catfish, Conven-tional.